Functionality and chemical stability of plasma polymer films exhibiting a vertical cross-linking gradient in their subsurface. (October 2018) - Vandenbossche, Marianne; Dorst, Johanna; Amberg, Martin; Schütz, Urs; Rupper, Patrick; Heuberger, Manfred; Hegemann, Dirk
Abstract: Preserving the amount of amine groups in a plasma polymer film (PPF) immersed in water is crucial for biomedical applications such as, e.g., bio-sensing or tissue engineering. In this study, nanometer thick PPFs were deposited on a substrate by activation of NH3 /C2 H4 gaseous mixtures in a low pressure plasma. In particular, plasma deposition conditions were adjusted during film growth to create a vertical gradient in amine group functionality and cross-linking degree extending over a few nanometers of the PPF near its surface. As a result of the vertical gradient structure, undesired changes in wettability, in chemical composition, in surface charge and in topology of the 'gradient' NH2 -PPF were strongly reduced as observed over one week in water. In comparison, 'conventional' coatings, i.e. deposited at constant plasma conditions yielding the same chemical composition as the top layer of the gradient structure, revealed distinct surface restructuring effects. Albeit oxidation of the coatings was found to be inevitable, the gradient structure significantly decreased these aging effects of the NH2 -PPF. To further highlight the benefits of the stabilizing structure in the coating's subsurface, investigations were carried out under flowing water conditions demonstrating the reduced degradation of the NH2 -PPFs with vertical cross-linking gradient for realistic conditions. Highlights: Amino group-containing plasma polymer films degrade when exposed to water. Stabilization of plasma polymer films by nanoscaled vertical gradients in cross-linking. The degradation is distinctly limited to the outermost nanometer by enhanced cross-linking in the subsurface. Chemical mechanism responsible for the stability of amino groups are discussed.